Role of ellagic acid against cisplatin-induced nephrotoxicity and oxidative stress in rats - Atessahin, Ahmet; Ceribasi, Ali Osman; Yuce, Abdurrauf; Bulmas, Ozgur; Cikim, Gurken (Blackwell Publishing, 2007)
The aim of this study was to investigate the possible protective role of antioxidant treatment with ellagic acid on cisplatin-induced nephrotoxicity using biochemical and histopatological approaches. Adult male Sprague-Dawley rats were randomly divided into four groups. The control group received 0.9% saline; animals in the ellagic acid group received only ellagic acid (10 mg/kg); animals in the cisplatin group received only cisplatin (7 mg/kg); animals in the cisplatin + ellagic acid group received ellagic acid for 10 days after cisplatin. The effects of ellagic acid on cisplatin-induced nephrotoxicity were evaluated by plasma creatinine, urea, sodium and calcium concentrations; kidney tissue malondialdehyde, reduced glutathione (GSH), glutathione peroxidase (GSH peroxidase) and catalase activities and histopatological examinations. Administration of cisplatin to rats induced a marked renal failure, characterized by significant increases in plasma creatinine, urea and calcium concentrations. Cisplatin also induced oxidative stress, as indicated by increased kidney tissue concentrations of malondialdehyde, and reduced activities of GSH peroxidase and catalase. Furthermore, treatment with cisplatin caused a marked tubular necrosis, degeneration and desquamation, luminal cast formation, karyomegaly, tubular dilatation, interstitial mononuclear cell infiltration and inter-tubular haemorrhagia. Ellagic acid markedly reduced elevated plasma creatinine, urea and calcium levels and counteracted the deleterious effects of cisplatin on oxidative stress markers. In the same way, ellagic acid ameliorated cisplatin-induced pathological changes including tubular necrosis, degeneration, karyomegaly, tubular dilatation when compared to the cisplatin alone group. These results indicate that the antioxidant ellagic acid might have a protective effect against cisplatin-induced nephrotoxicity and oxidative stress in rat, but not enough to inhibit cisplatin-induced renal dysfunction.
Keywords: Vitamin-E Succinate; Lipid-Peroxidation; Antioxidant Activity; Induced Toxicity; in-Vitro; Protection; Selenium; Mice; Mutagenicity; Pomegranate